BIOEFFICACY POTENTIAL OF TRIFLUMEZOPYRIM FOR THE MANAGEMENT OF RICE PLANTHOPPERS - SURI, K. S.; MAKKAR, GURPREET SINGH (The Bioscan, 2018)
This is the first report on bioefficacy of triflumezopyrim 10.6 SC, an insecticide of mesoionic chemical class, against rice planthoppers, Nilaparvata lugens and Sogatella furcifera from the Punjab. Triflumezopyrim 10.6 SC was evaluated @ 5, 15, 25, 35, 50 and 100 g a.i. ha-1 and compared with the checks, imidacloprid 17.8 SL and buprofezin 25 SC @ 20 and 200 g a.i. ha-1, respectively. Triflumezopyrim 10.6 SC @ 35 and 25 g a.i. ha-1 proved significantly superior to all other treatments at 3 days after spray (2.54 and 2.60 hoppers/hill, respectively), 7 DAS (1.98 and 1.99 hoppers/hill, respectively) and 14 DAS (2.43 and 2.48 hoppers/hill, respectively) in controlling the BPH population, however after 10 DAS, buprofezin 25 SC proved at par with triflumezopyrim 10.6 SC @ 25 g a.i. ha-1, indicating the slow action of buprofezin. A similar trend, confirming superiority of triflumezopyrim 10.6 SC @ 35 and 25 g a.i. ha-1 over other treatments was recorded after 3 DAS (1.96 and 1.98 hoppers/hill, respectively) and 10 DAS (1.78 and 1.82 hoppers/hill, respectively) in controlling WBPH. The test insecticide was also found safe, without any observable phytotoxicity symptoms on rice. Thus, triflumezopyrim 10.6 SC @ 25 g a.i. ha-1 may be effectively used for the control of rice planthoppers.